2016
DOI: 10.1016/j.bbr.2016.05.032
|View full text |Cite
|
Sign up to set email alerts
|

A bout analysis reveals age-related methylmercury neurotoxicity and nimodipine neuroprotection

Abstract: Age-related deficits in motor and cognitive functioning may be driven by perturbations in calcium (Ca2+) homeostasis in nerve terminals, mechanisms that are also thought to mediate the neurotoxicity of methylmercury (MeHg). Calcium-channel blockers (CCBs) protect against MeHg toxicity in adult mice, but little is known about their efficacy in other age groups. Two age groups of BALB/c mice were exposed to 0 or 1.2 mg/kg/day MeHg and 0 or 20 mg/kg/day of the CCB nimodipine for approximately 8.5 months. Adults b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 76 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…To ensure that the doses of nimodipine used both in vivo and in vitro in our study were clinically relevant, we followed the recommendations in published studies (6, 13, 18, 50, 51). All doses described in the quoted literature were able to attenuate cognitive deficits in models of neurodegenerative diseases and to trigger endogenous hormone responses, so it is likely that sufficient levels of the drug were achieved in the CNS (13,50,52). Furthermore, many studies on subarachnoidal hemorrhage have shown that the dosages used in animal studies are able to induce comparable effects in patients (51, 52).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure that the doses of nimodipine used both in vivo and in vitro in our study were clinically relevant, we followed the recommendations in published studies (6, 13, 18, 50, 51). All doses described in the quoted literature were able to attenuate cognitive deficits in models of neurodegenerative diseases and to trigger endogenous hormone responses, so it is likely that sufficient levels of the drug were achieved in the CNS (13,50,52). Furthermore, many studies on subarachnoidal hemorrhage have shown that the dosages used in animal studies are able to induce comparable effects in patients (51, 52).…”
Section: Methodsmentioning
confidence: 99%
“…Proapoptotic effects of DMSO or ethanol alone were also excluded by performing corresponding vehicle-control experiments. To ensure that our in vitro dose of nimodipine was clinically relevant, we studied the literature closely and tested doses that already had been used in several CNS disease models (13,18,50,51). The dose used for cell culture had been shown to induce equivalent effects in patients (e.g., reduced stress-mediated effects after brain surgery and decreased excitotoxicity) (51).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Ming et al 21 showed that nimodipine (Nim), a dihydropyridine Ca 2+ antagonist, could activate neuroprotective signaling events to protect the brain. Despite the mounting evidence showing that Nim has a direct effect on neurons, has neuropharmacological and psychopharmacological efficacy, and can protect and promote memory and cognitive recovery., 21,22 there are few reports regarding the effects of Nim on learning and memory impairment caused by exposure to PAEs.…”
Section: Introductionmentioning
confidence: 99%